Library Publishing Toolkit edited by Allison P. Brown - Deborah Barreau (Journal of Librarianship and Scholarly Communication, 2013)
The “library as publisher” is a hot topic right now in both public and academic libraries. From promoting open access to providing patrons with new services to meet a growing demand, libraries are rising to the challenge of moving from being consumers and providers of information to becoming publishers of information. For those libraries who are interested in learning more, or are implementing such programs at their institutions, the Library Publishing Toolkit serves as an excellent guide.